STRATEGI KEPALA SEKOLAH MEMBANGUN BRAND IMAGE MENUJU SEKOLAH UNGGUL BERKOLABORATIF PADA SEKOLAH MENENGAH PERTAMA (SMP) - Zuriati, Zuriati; Mulyadi, Said; Marsithah, Iis (Hijri, 2024)
This study aims to analyze the strategies is used by school principals to creat a brand image going to a collaborative of excellent school in Junior High Schools (SMP) in North Aceh, specially at SMPN 2 Meurah Mulia and SMPN 7 Sawang. The study uses four innovative strategies implemented by the principals: facilitative strategies, educational strategies, persuasive strategies, and coercive strategies. The research uses a qualitative approach with data collection techniques including interviews, observations, and document reviews. The research subjects consist of principals, teachers, students, the school committee, and supervisors at the two schools being studied. The results indicate that facilitative strategies have successfully created the schools' brand image as excellent and collaborative institutions at SMPN 2 Meurah Mulia and SMPN 7 Sawang. This success is reflected in student achievements, facility management, and partnerships with external communities. However, educational strategies have not yet been fully effective in creating the desired brand image, particularly at SMPN 2 Meurah Mulia, where challenges in implementing changes and motivating teachers still limited. Meanwhile, persuasive strategies applied at both schools have successfully increased the participation of the school community and parents, thereby supporting the strengthening of the schools' brand image. Furthermore, coercive strategies have also proven effective in enhancing discipline and participation, thereby strengthening the schools' reputation in the community. This study concludes that success in creating a brand image going to a collaborative excellent school requires a combination of various innovative educational strategies, including facilitative, educational, persuasive, and coercive strategies, with an emphasis on collaboration, communication, and adaptation to existing challenges.